Стан наукового дослідження проблем розслідування кримінальних правопорушень, пов’язаних із домашнім насильством - Гонтаренко, В. П.; Hontarenko, V. P.; ORCID: http://orcid.org/0000-0001-7575-8914 (Право і безпека. – 2022. – № 1 (84). – С. 241-250, 2022)
Висвітлено історичні та сучасні тенденції розвитку наукової думки щодо протидії домашньому насильству. Досліджено зміну підходів до розуміння понять «домашнє насильство» та «правопорушення, пов’язані з домашнім насильством». На підставі змістовного співвідношення вказаних категорій з’ясовано тенденції розвитку наукової думки щодо протидії цим правопорушенням, передусім кримінально-правового характеру. Акцент зроблено на висвітленні досягнень українських науковців, зокрема тих наукових праць, що присвячені проблемам досудового розслідування кримінальних правопорушень, пов’язаних із домашнім насильством, за результатами аналізу яких запропоновано авторську періодизацію розвитку наукової думки за темою дослідження.

An attempt was made to trace the change in approaches to the understanding of the concepts of “domestic violence” and “offenses related to domestic violence” and, based on the meaningful correlation of these categories, to reveal the trends in the development of scientific opinion on countering these offenses, primarily of a criminal law nature. Emphasis is placed on highlighting the achievements of Ukrainian scientists in works devoted to the problems of pre-trial investigation of criminal offenses related to domestic violence. Based on the results of the analysis, the author's periodization of the development of scientific thought in the specified field has been proposed. As a result of the conducted research, some regularities of the development of the criminal procedural opinion based on the research of the problems of pre-trial investigation of criminal offenses related to domestic violence have been outlined. The first conclusion indicates the gradual development of such studies, which is connected with the change of the material and legal basis, that is, the criminal legislation, which at different times provided a different qualifying model of criminal offenses related to domestic violence. Thus, at the first stage (until 2017), domestic scientists mostly directed their attention to the study of criminal law and criminological problems of combating criminal offenses included in the concept of “crimes related to domestic violence”. There are only separate works of a criminal procedural or forensic nature, aimed at solving the problems of investigating a set of types of criminal offenses included in the concept of “crimes related to domestic violence”. The next stage (since 2017) is related to the criminalization of domestic violence (Article 126-1 “Domestic Violence” was added to the Special Part of the Criminal Code of Ukraine). It is natural that the specified event aroused interest among scientists and, in particular, shifted the emphasis of scientific research to the problems of investigating domestic violence within the scope of one crime. Currently, the beginning of the transition to the third stage of the development of scientific research on the problems of investigating criminal offenses related to domestic violence is observed. The latter is characterized by a shift in the emphasis of scientists to researching the problems of investigating other types of criminal offenses related to domestic violence, other than those provided for in Art. 126-1 “Domestic violence” of the Criminal Code of Ukraine, for example, a study of the problems of investigating murders committed with the use of domestic violence.

Освещены исторические и современные тенденции развития научной мысли в сфере борьбы с домашним насилием. Прослежено изменение подходов к пониманию понятий «домашнее насилие» и «правонарушения, связанные с домашним насилием». На основании содержательного соотношения этих категорий раскрыто тенденции развития научной мысли относительно противодействия этим правонарушениям, прежде всего уголовно-правового характера. Акцент сделан на освещении достижений украинских ученых в работах, посвященных проблемам досудебного расследования уголовных правонарушений, связанных с домашним насилием, и по результатам анализа которых предложена авторская периодизация развития научной мысли в этой сфере.
The state of scientific research on the problems of investigating criminal offenses related to domestic violence
Состояние научного исследования проблем расследования уголовных правонарушений, связанных с домашним насилием
Гонтаренко, В. П. Стан наукового дослідження проблем розслідування кримінальних правопорушень, пов’язаних із домашнім насильством / В’ячеслав Петрович Гонтаренко // Право і безпека. – 2022. – № 1 (84). – С. 241-250. – DOI: https://doi.org/10.32631/pb.2022.1.25.
Гонтаренко В. П. Стан наукового дослідження проблем роз- слідування кримінальних правопорушень, пов’язаних із домашнім насильством . Право і безпека . 2022. No 1 (84). С. 241– 250. DOI: htt ps ://doi.org/ 10.32631/ pb.2022.1.25.
Gontarenko , V. P. (2022). The state of scientific research on the problems of investigating criminal offenses related to domestic violence . Law and Safety, 1 (84), 241– 250 . htt ps ://doi.org/ 10.3263 1/ pb.2022.1.25.
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; домашнє насильство; досудове розслідування; розвиток наукової думки; domestic violence; pre-trial investigation; development of scientific thought; домашнее насилие; досудебное расследование; развитие научной мысли